Model Pengembangan Organisasi dalam Mendukung Efektivitas Sumber Daya Manusia Melalui Analisis Jabatan dan Analisis Beban Kerja - Prastika Prastika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Digital transformation in public service organizations has changed job design, business processes, task distribution, and employee competency requirements. This study aims to analyze the application of job analysis and workload analysis as a basis for human resource restructuring in response to these changes. The study employed a descriptive design with a qualitative approach supported by quantitative workload analysis. It covered all work units within a public service organization in Jakarta, Indonesia. Data were collected through document analysis, semi-structured interviews, non-participant observation, job analysis questionnaires, and workload analysis forms. The findings indicate that digitalization has transformed administrative activities, data management, supervision, and reporting processes. Consequently, each position requires technical, administrative, communication, and technological adaptability competencies. The workload analysis also identified an uneven distribution of work across positions. Several positions experienced excessive workloads, whereas others were not optimally utilized. These conditions were influenced by differences in work volume, task complexity, service intensity, and the level of adaptation to digital systems. The study concludes that integrating job analysis and workload analysis is necessary to align job descriptions, competencies, work distribution, and staffing requirements. The analysis provides an empirical basis for task redistribution, workforce adjustment, job competency updates, and continuous digital competency development.